Phononic Crystals: Phononic Crystal with Adaptive Connectivity (Adv. Mater. 9/2014). (March 2014) - Bergamini, Andrea; Delpero, Tommaso; Simoni, Luca De; Lillo, Luigi Di; Ruzzene, Massimo; Ermanni, Paolo
<x xml:space="preserve">Abstract</x> Phononic crystals are structures with discontinuous dispersion relations, such as crystals made of atoms. A. Bergamini and co‐workers show on page 1343 that in adaptively augmented phononic crystals, existing bandgaps can be canceled at specific frequencies by modifying the mechanical connectivity of the unit cell. Photography: Wolfram Raither, ETH Zürich Photo Design: Beat Geyer, Empa and Wolfram Raither, ETH Zürich. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>